2021
DOI: 10.17268/sci.agropecu.2021.016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the 5s rDNA locus in Physalis peruvianaL. chromosomes, first report

Abstract: Identification of the 5s rDNA locus in Physalis peruviana L. chromosomes, first report Primer reporte sobre identificación del locus 5s rADN en cromosomas de Physalis peruviana L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This is consistent with the findings of the current study, which found a predominance of six 5s rDNA sites in all goldenberry populations, with a small fraction of four and seven sites in the cultivated populations (Figure 3). Similarly, Siles et al (2021) discovered a prevalence of six 5s rDNA sites in goldenberry cultivated populations. However, other Solanaceae species have a lower number of 5s rDNA sites, such as Solanum spp., which has a prevalence of two 5s rDNA sites and, to a lesser extent, four sites (Pendinen et al 2008;Rego et al 2009;Aguilera et al 2016;Romero-da et al 2017), Capsicum spp., which typically presents two sites (Youn-Kyu et al 1999;Park et al 2000;Kwon and Kim 2009;Aguilera et al 2016;Romero-da et al 2017); Nicotiana spp., which generally alternates between two and four sites (Nakamura et al 2001;Kitamura et al 2001;Fulneček et al 2002;Matyasek et al 2003;Kovarik et al 2004), and Cestrum spp., which has two 5s rDNA sites (Fregonezi et al 2006;Fernandes et al 2009;Urdampilleta et al 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is consistent with the findings of the current study, which found a predominance of six 5s rDNA sites in all goldenberry populations, with a small fraction of four and seven sites in the cultivated populations (Figure 3). Similarly, Siles et al (2021) discovered a prevalence of six 5s rDNA sites in goldenberry cultivated populations. However, other Solanaceae species have a lower number of 5s rDNA sites, such as Solanum spp., which has a prevalence of two 5s rDNA sites and, to a lesser extent, four sites (Pendinen et al 2008;Rego et al 2009;Aguilera et al 2016;Romero-da et al 2017), Capsicum spp., which typically presents two sites (Youn-Kyu et al 1999;Park et al 2000;Kwon and Kim 2009;Aguilera et al 2016;Romero-da et al 2017); Nicotiana spp., which generally alternates between two and four sites (Nakamura et al 2001;Kitamura et al 2001;Fulneček et al 2002;Matyasek et al 2003;Kovarik et al 2004), and Cestrum spp., which has two 5s rDNA sites (Fregonezi et al 2006;Fernandes et al 2009;Urdampilleta et al 2014).…”
Section: Discussionmentioning
confidence: 94%
“…This is due to the nature of rDNA sequences, which are tandemly repeated DNA regions in the genome with high transcription rates and a predisposition for unequal recombination, which makes them inherently unstable and prone to variation in copy number and location in the genome (Salim and Gerton 2019). Previously, the number of 5s rDNA signals in two cultivated populations from the same region has been studied at the molecular cytogenetic level in Physalis peruviana L. (Siles et al 2021). However, no studies have been conducted to analyze the number and position of the 5s and 45s rDNA sites to determine if there are any chromosomal differences between wild and cultivated populations as a consequence of the domestication of the species.…”
Section: Introductionmentioning
confidence: 99%
“…The most cultivated P. peruviana ecotypes in the world are Kenya, South Africa, and Colombia. In Peru, there are four ecotypes from the Cajamarca region [38], and they constitute the genetic basis of the world's commercial crops. In Peru, P. peruviana is distributed in the Yunga and Quechua regions (2000 and 2500 meters above the mean sea level, respectively) [9], and the agricultural production areas are Ancash, Ayacucho, Cajamarca (main producing area), and Cusco [37].…”
Section: Introductionmentioning
confidence: 99%
“…peruviana is one of the "Superfoods Peru" because of its important nutritional properties and health benefits, which has boosted its agricultural production for export. Recently, studies on the genetic characterization and molecular cytogenetics of fruits grown in Peru have been conducted [9,38] to understand the biological and genetic diversity of this species. However, there are only a few studies that refer to the chemical composition and nutritional and antioxidant capacity of P. peruviana cultivated in Peru [20,25].…”
Section: Introductionmentioning
confidence: 99%